Geometric control of sliding friction. (November 2021) - Liefferink, Rinse W.; Weber, Bart; Coulais, Corentin; Bonn, Daniel
Abstract: Controlling and predicting friction is a significant scientific and technological issue. It is our everyday experience that two smooth surfaces slide more easily over each other than two rough ones, due to interlocking of the rough surfaces. However, the interpretation of such friction forces is difficult since other contributions arise from e.g. adhesion forces, that are harder to control. Here, we demonstrate that designer macroscopic roughness can be used to control, dynamically tune and quantitatively predict friction. We show that the roughness allows to tune the friction coefficient by more than an order of magnitude, which can be explained completely by a simple Coulombic friction model. A kirigami metamaterial surface with externally tunable roughness allows us to show that this understanding of geometrical friction can be used to control on-the-fly the friction in a single system by dynamically controlling its roughness.